Perbedaan Hasil Derajat Aglutinasi Serum Grouping Tube Test Dengan Suspensi Reagen NaCl 0,9% Siap Pakai dan Suspensi Reagen NaCl 0,9% Dari Garam Dapur - Hani Ammariah; Nurhidayanti Nurhidayanti; Bastian Bastian; Trimin Kartika (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2022)
ABO blood group examination is a simple laboratory test performed to determine a person’s blood group. There are two types of ABO blood group test, namely cell grouping and serum grouping. Serum grouping examination is very important to prevent incompatible transfusion reactions and organ transplant rejection. Serum grouping was carried out using 10% saline wash suspension of cell A, B and O. The blood cell washing stage was used to remove fragile cells and interfering substances that could result in errors in the examination. The main ingredient used in the blood cell washing procedur is 0.9% NaCl. This study aims to determine the degree of agglutination serum grouping tube test with ready to use 0.9% NaCl reagent suspension and 0.9% NaCl reagent suspension from table salt. The type of research is an experiment. The study was conducted at UDD PMI South Sumatra Province on 30 December 2021 to 5 January 2022 with a totalsample of 67 samples. The results showed that the average degree of agglutination the serum grouping tube test with 0.9% NaCl reagent ready to use was 3.73 and the average degree of agglutination the serum grouping tube test with0.9% NaCl reagent from table salt was 3.69. Wilcoxon test results obtained p value = 0.450. The conclusion of the study, that there is no differences in the results of the agglutination serum grouping tube test with ready to use 0.9% NaCl reagen suspension and 0.9% NaCl reagent suspension from table salt. The table salt showed that 0.9% NaCl reagent can be used as alternative reagent NaCl 0.9% ready to use in the examination of Iserum grouping tube test.